1982
DOI: 10.1021/bi00261a011
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of parathyroid hormone by Kupffer cells: analysis by reverse-phase high-performance liquid chromatography

Abstract: Parathyroid hormone (PTH) undergoes rapid proteolysis in the liver, which results in the appearance of multiple COOH-terminal fragments in plasma. Using reverse-phase high-performance liquid chromatographic (HPLC) techniques, we have shown that biologically active bovine PTH (bPTH) internally labeled with [3H]tyrosine is, like 125I-labeled bPTH, rapidly metabolized by isolated rat Kupffer cells in vitro to multiple COOH-terminal fragments that are chemically identical with those previously found in plasma afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…It is also interesting to consider that the differences in the C-terminal regions of the two ligands account, to some extent, for the distinct modalities by which the two ligands carry out their biologic functions-i.e., the endocrine modality by which PTH controls Ca and Pi homeostasis versus the paracrine modality by which PTHrP controls cell differentiation programs. For PTH, it has been shown that C-terminal peptide fragments derived from the secreted hormone can be detected in the circulation (Bringhurst et al, 1982;D'Amour et al, 2005), and synthetic C-terminal fragments can bind with moderate affinities to some non-PTHR1, but as yet unidentified binding sites in cultured cells (Divieti et al, 2005). There is thus possibility that the C-terminal domains of PTH and PTHrP can function autonomously and independently of the PTHR1.…”
Section: B Parathyroid Hormone-related Proteinmentioning
confidence: 99%
“…It is also interesting to consider that the differences in the C-terminal regions of the two ligands account, to some extent, for the distinct modalities by which the two ligands carry out their biologic functions-i.e., the endocrine modality by which PTH controls Ca and Pi homeostasis versus the paracrine modality by which PTHrP controls cell differentiation programs. For PTH, it has been shown that C-terminal peptide fragments derived from the secreted hormone can be detected in the circulation (Bringhurst et al, 1982;D'Amour et al, 2005), and synthetic C-terminal fragments can bind with moderate affinities to some non-PTHR1, but as yet unidentified binding sites in cultured cells (Divieti et al, 2005). There is thus possibility that the C-terminal domains of PTH and PTHrP can function autonomously and independently of the PTHR1.…”
Section: B Parathyroid Hormone-related Proteinmentioning
confidence: 99%
“…Most early assays were directed against the middle or C-terminus of the PTH peptide (2). Investigators soon found that several fragments of PTH in serum were derived from the parathyroid glands and from peripheral metabolism of PTH(1-84) (3)(4)(5)(6)(7)(8)(9)(10)(11). The later development of a 2-site radioimmunometric assay allowed measurement of primarily intact PTH(1-84) (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In the Kupffer cells of the liver, the whole PTH molecule undergoes a fast metabolism. The whole (1-84)PTH molecule is split up into various fragments [13][14][15][16]. These fragments are afterwards eliminated by the kidney.…”
Section: Discussionmentioning
confidence: 99%